Synthesis, Characterization and Antimicrobial Screening of Some 4-Acylpyrazoloimines and Some 3d Transition Metal(II) Complexes - Asegbeloyin, J.N.; Okafor, E.C.; Ukwueze, N.N.; Babahan, I.; Agbo, I.C. (Asian Journal of Chemistry, 2014)
Some 4-acylpyrazoloimines and their 3d transition metal(II) complexes have been synthesized. The ligands and their 3d transition metal complexes were characterized by elemental analysis, molar conductance, magnetic susceptibility measurements and spectroscopic methods. The ligands behaved as mono-anion ONO or ONS donor molecules. Microanalysis, electronic spectral and magnetic measurements showed the metal complexes as ML2 type. All the synthesized compounds were screened for their in vitro antimicrobial activity against some gram positive and gram negative clinical bacterial strains. Antimicrobial activity test results showed that the metallic derivatives are more active against the bacterial strains than the imines.